Serological follow up of positive SARS-CoV-2 cases - José Gerardo González-González; Adrián Camacho-Ortiz; René Rodríguez-Gutiérrez; Donato Saldívar-Rodríguez; Luz Adriana Ramírez-García; Adriana Sánchez-García (Instituto Nacional de Salud Pública, 2022)
Objective. To describe the humoral response in a cohort with mild and asymptomatic SARS-CoV-2 infection previously identified in a community-based serological survey. Materials and methods. This study was an observational follow up of 193 subjects previously identified with positive anti-SARS-CoV-2 antibodies invited for a second test 112 days after the first sampling. All completed a standardized electronic questionnaire. IgM/IgG antibodies were determined using a qualitative IgM/IgG chemiluminescent immunoassay. Results. Among the 193 eligible subjects, a total of 174 (90%) attended the follow-up visit, and their serum samples were tested. Of the samples, 171 (98.3%) were still positive, and 3 (1.7%) were negative. Also, the cut-off index (COI) value of the immunoassay significantly increased from the first to the second test (P <0.001). Conclusions. Our findings support a sustained humoral response in individuals with mild and asymptomatic SARS-CoV-2 infection up to 112 days after a positive serologic baseline test, accompanied by increasing antibody titers.